Acquiring English Vocabulary at Children Aged 9-11 Years Old During Covid-19 Pandemic - Andri Donal; Nirwana Syahputra (English Education Study Program Faculty of Teacher Training and Education, 2021)
Covid19 pandemic has changed the education system. Almost all educational institutions reduced face to face learning and applied online learning. The Indonesian government supports this system by providing internet credit subsidies to students and teachers. It triggers students to often use gadgets such as learning, playing online games, or browsing internet sites. One of the impacts of this pandemic period is the process of English Language Acquisition in children. The purpose of this study was to determine the process of acquiring English vocabulary and kinds of English vocabulary in children aged around 9-11 years. The researchers applied descriptive qualitative study by involving three participants aged 9,10,11 year old. To get more valid data, researchers observed participant activities, especially how their English vocabulary was obtained and the English vocabulary was what they produced. In addition to deepening data, researchers also conducted semi-structural interviews to participants. Interviews were also carried out to determine the extent to which they understood the English vocabulary they produced. The results showed that there were several ways children to obtain English vocabulary during Covid 19 pandemic, imitating someone's words, hearing or reading from online games, listening to music, watching television, and reading vocabulary on food wrap. The types of English vocabulary they get are nouns, verbs, adjectives, and adverbs. It can be concluded that children acquired English vocabularies during the Covid 19 pandemic which is one of the consequences of the use of gadgets that must be for learning activities. However, there are some English vocabularies that are still taboo for them. The results of this study are expected to increase parents' awareness in overseeing the use of gadgets for children because not all English vocabulary they get is in accordance with Indonesian culture.